Vulnerabilities in Social Assistance System - BREAZ, MARIA-ALINA (Presa Universitară Clujeană, 2024)
In recent years, Romania has made significant progress in various aspects of its social and economic development. However, one pressing issue that continues to demand attention is the well-being of its vulnerable children. Despite efforts to improve the situation, many children in Romania still face a range of challenges that affect their development, education, and future prospects. One of the major issues is the high number of children living in poverty. Economic disparities in the country have left a substantial portion of the population struggling to meet basic needs.